Bacterial keratitis caused by Kocuria varians: a case report (Ukrainian Journal of Ophthalmology, 2023)
The purpose of this paper is to report a rare case of bacterial keratitis caused by the non-pathogenic Kocuria varians. The case reported exemplifies the development of severe bacterial keratitis following a corneal microtrauma induced by of non-pathogenic or potentially pathogenic species. We report a rare cause of Kocuria varians keratitis in a review of national and foreign literature. Examination of the corneal microbiota and determination of its spectrum of sensitivity to antibiotics, if performed early, will facilitate the administration of adequate treatment and prevention of severe complications in corneal bacterial lesions.
Keywords: keratitis; Kocuria varians; clinical manifestations; treatment